2018
DOI: 10.1016/j.jacbts.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramides as Prognostic Biomarkers and Their Arterial and Myocardial Tissue Correlates in Acute Myocardial Infarction

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
58
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 42 publications
7
58
1
4
Order By: Relevance
“…Recently, de Carvalho et al showed myocardial upregulation of three ceramide-producing enzymes (i.e., ceramide synthase 6, serine palmitoyl transferase-2, and neutral sphingomyelinase) in a rodent model of acute myocardial infarction after LAD ligation. In this animal model, there was a net increase in production of long-chain ceramides [mainly Cer(d18:1/20:0), Cer(d18:1/22:0) and Cer(d18:1/24:0)] [24]. Collectively, these experimental findings may help also shed light on the results of our study that showed a strong association between increased levels of these plasma ceramides and severity of LAD stenosis.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, de Carvalho et al showed myocardial upregulation of three ceramide-producing enzymes (i.e., ceramide synthase 6, serine palmitoyl transferase-2, and neutral sphingomyelinase) in a rodent model of acute myocardial infarction after LAD ligation. In this animal model, there was a net increase in production of long-chain ceramides [mainly Cer(d18:1/20:0), Cer(d18:1/22:0) and Cer(d18:1/24:0)] [24]. Collectively, these experimental findings may help also shed light on the results of our study that showed a strong association between increased levels of these plasma ceramides and severity of LAD stenosis.…”
Section: Discussionsupporting
confidence: 73%
“…Growing evidence suggests that the blood levels of ceramides are associated with the exacerbation of myocardial ischemic disease and its complications 7,40,49 . Studies on murine models revealed that pharmacological inhibition of the synthesis of ceramides prevents heart failure after myocardial ischemia, decreasing ventricular remodeling, fibrosis, and inflammatory infiltrate 8,43,50 . Similarly, the administration of an inhibitor of neutral SMases which hydrolyzes sphingomyelin to ceramide, thus impairing EV biogenesis, namely GW4869, reduced the increase of circulating inflammatory EV after MI in rats, resulting in the preservation of left ventricular ejection fraction 27 .…”
Section: Discussionmentioning
confidence: 99%
“…transfer proteins may then further participate in exchange of ceramides between the circulating lipoproteins. Another source of circulating ceramides has been suggested to be an ischemic myocardial tissue, which thereby may contribute to an increase in the plasma levels of ceramides after an acute myocardial infarction [4]. This suggestion is supported by observations in rat models with myocardial ischemia showing that together with increased myocardial ceramide levels also the plasma levels of ceramides are increased [4,19,20].…”
mentioning
confidence: 99%
“…Plasma ceramides (CER), a class of sphingolipid molecules, have been identified as markers of future cardiovascular (CV) events and measurement of certain ceramide species and their ratios in plasma samples can predict major acute CV events and CV mortality [1][2][3][4]. The data suggest that plasma ceramide levels may predict CV events more accurately than traditional risk biomarkers at least in patients with known atherosclerotic CV disease (CVD).…”
mentioning
confidence: 99%
See 1 more Smart Citation